Perception of global problems among students an 8-year retrospective - Berényi László (Proceedings of the International Symposium on Analytical and Environmental Problems, 2024)
Global social and environmental problems frame the development actions for sustainability. UN conferences and other sources display a long list of problems, which enhances the evaluation of the relative importance of the items. The paper presents the results of empirical data collection among higher education students about their preferences between 2016 and 2024. The results show that the perception of the most critical global problems is differently assessed in their local environment and worldwide. Some changes in the orders were found, especially before and after 2020, but there was no fundamental change in the opinions.